Ð“Ð¸ÑÑ‚Ð¾Ð»Ð¾Ð³Ð¸Ñ‡ÐµÑÐºÐ¸Ð¹ Ð°Ð½Ð°Ð»Ð¸Ð· Ð¸Ð·Ð¼ÐµÐ½ÐµÐ½Ð¸Ð¹ Ñ‚ÐºÐ°Ð½ÐµÐ¹ Ð³Ð¾Ð»Ð¾Ð²Ð½Ð¾Ð³Ð¾ Ð¼Ð¾Ð·Ð³Ð° ÐºÑ€Ñ‹Ñ Ñ ÑÐºÑÐ¿ÐµÑ€Ð¸Ð¼ÐµÐ½Ñ‚Ð°Ð»ÑŒÐ½Ñ‹Ð¼ Ð¿Ð°Ñ€ÐºÐ¸Ð½ÑÐ¾Ð½Ð¸Ð·Ð¼Ð¾Ð¼ Ð´Ð¾ Ð¸ Ð¿Ð¾ÑÐ»Ðµ Ñ‚Ñ€Ð°Ð½ÑÐ¿Ð»Ð°Ð½Ñ‚Ð°Ñ†Ð¸Ð¸ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… ÑÐ¼Ð±Ñ€Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ñ‹Ñ… Ð½ÐµÑ€Ð²Ð½Ñ‹Ñ… ÐºÐ»ÐµÑ‚Ð¾Ðº - Pyatikop, V. A.; Karamyshev, V. D.; Shevereva, V. M.; Dvortsevoy, V. K. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
There are presented histomorphological characteristics of cryopreserved embryonic nerve cells (ENCs) transplants in rats with experimental parkinsonism, induced by bilateral anode electrolysis of substantia nigra. Engrafted ENCs were shown to proliferate within the introduction area and beyond the scar. The introduced neuroblasts are spread beyond the proliferation area as well.